miR-1260b inhibits periodontal bone loss by targeting ATF6β mediated regulation of ER stress - Hayashi, Chikako; Fukuda, Takao; Kawakami, Kentaro; Toyoda, Masaaki; Nakao, Yuki; Watanabe, Yukari; Shinjo, Takanori; Sano, Tomomi; Iwashita, Misaki; Yotsumoto, Karen; Shida, Miyu; Taketomi, Takaharu; et al. (Frontiers in Cell and Developmental Biology, 2022)
The expression profiles of exosomal microRNAs (miRNAs) are regulated by the microenvironment, and appropriate priming with mesenchymal stem cells (MSCs) is one of the strategies to enhance the paracrine potency of MSCs. Our previous work demonstrated that exosomes from tumor necrosis factor (TNF)-α-primed human gingiva-derived MSCs (GMSCs) could be a therapeutic tool against periodontitis, and that TNFα-inducible exosomal miR-1260b is essential for the inhibition of alveolar bone loss. However, the precise molecular mechanism underlying miR-1260b-mediated inhibition of osteoclastogenesis is not yet fully understood. Here, we found that the activating transcription factor (ATF)-6β, a novel miR-1260b-targeting gene, is critical for the regulation of osteoclastogenesis under endoplasmic reticulum (ER) stress. An experimental periodontal mouse model demonstrated that induction of ER stress was accompanied by enhanced ATF6 expression, and local administration of miR-1260b and ATF6β siRNA using polyethylenimine nanoparticles (PEI-NPs) significantly suppressed the periodontal bone resorption. In periodontal ligament (PDL) cells, the ER stress inducer, tunicamycin, enhanced the expression of the receptor activator of NF-κB ligand (RANKL), while miR-1260b-mediated downregulation of ATF6β caused RANKL inhibition. Furthermore, the secretome from miR-1260b/ATF6β-axis-activated PDL cells inhibited osteoclastogenesis in human CD14+ peripheral blood-derived monocytes. These results indicate that the miR-1260b/ATF6β axis mediates the regulation of ER stress, which may be used as a novel therapeutic strategy to treat periodontal disease.